A passive Digital footprint for Extranet environment - Harith A. Hussein (Al-Qadisiyah Journal of Pure Science, 2018)
Within both Extranet and Intranet, security and privacy is the greatest importance and a breach could result a tragedy. Maintaining these two aspects are the primary challenge within organization. Bothe Extranet and Intranet are attractive to a lot of organizations, because they can significantly decrease the transaction and management charges among themselves and their customers, vendors, partners or suppliers. However, the same technology that brings benefits can also put an organization at risk if the proper security mechanisms are not in place. Meanwhile, Organization gives too much attention to avoid external threats, a little attention is being paid to internal threats. Moreover, Access control and authentication technology ensure that the user is who or she claims to be, but it is in the same time says nothing about cheated identity or the individual’s access rights. Thus, propose or present an access log that can log many information that can be used with further studies as auditing or monitoring system in order to track the internal staff digital footprint and finally predict or prevent the internal threat.The web logger, can log information's and track user's digital footprint passively around the sites, logged information include user access time and date, user IP address, username, user authentication type, accessed resources, how long they stay within this resources and finally, browser type.